2005
DOI: 10.1093/beheco/ari036
|View full text |Cite
|
Sign up to set email alerts
|

Diel activity and home range size in relation to food supply in a drift-feeding stream fish

Abstract: Individuals within a species often compete for resources in both space and time. In dominance hierarchies individuals with the greatest competitive ability will occupy prime locations during optimal periods. We compared spatial and temporal use of habitat, aggression, and feeding success among giant kokopu (Galaxias argenteus) in dominance hierarchies under normal and reduced food supply. Under normal food supply conditions dominant fish were predominantly nocturnal and maintained large home ranges at night. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
0
48
2
Order By: Relevance
“…In Alex Stream, cased caddis are the preferred food of the dominant drift-feeding fish, giant kokopu (Hansen et al, 2004), and the biomass of giant kokopu and the size of the dominant fish within stream pools is positively related to long-term drift density (Hansen, 2005). Assemblages of drift-feeding salmonid and galaxiid fish in stream pools are frequently highly stable through time, and the predictability of food supply may be critical for the formation of social hierarchies and long-term residency of the most profitable positions by dominant fish (Bachman, 1984;Hughes, 1992;David & Closs, 2003;David & Stoffels, 2003;Hansen & Closs, 2005). Significant results highlighted with an * Fig.…”
Section: Invertebrate Drift In Relation To Other Stream Organismsmentioning
confidence: 99%
“…In Alex Stream, cased caddis are the preferred food of the dominant drift-feeding fish, giant kokopu (Hansen et al, 2004), and the biomass of giant kokopu and the size of the dominant fish within stream pools is positively related to long-term drift density (Hansen, 2005). Assemblages of drift-feeding salmonid and galaxiid fish in stream pools are frequently highly stable through time, and the predictability of food supply may be critical for the formation of social hierarchies and long-term residency of the most profitable positions by dominant fish (Bachman, 1984;Hughes, 1992;David & Closs, 2003;David & Stoffels, 2003;Hansen & Closs, 2005). Significant results highlighted with an * Fig.…”
Section: Invertebrate Drift In Relation To Other Stream Organismsmentioning
confidence: 99%
“…feeding, reproduction and shelter). However, many studies have shown that movement patterns in a given area are positively related to feeding requirements and food availability (Huey & Pianka 1981), territoriality (Hansen & Closs 2005), stream/river size (Woolnough et al 2009) and fish body size (Haskell et al 2002) among others. In the present study we did not find correlation between fish size (expressed as fish standard length) and home range, but the other characters previously mentioned were not tested due to the absence of data concerning those life history attributes for Mata Atlântica streams.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing fragmentation of water bodies worldwide, knowledge about the extension of the habitat used by fish species is imperative (Downing et al 2006). It has been observed that in temperate regions, factors such as time of the year, reproductive season and environmental characters are important in defining movement patterns of stream-dwelling fishes and could be responsible for temporal patterns of community structure as well (Hansen & Closs 2005). Few studies concerning movement patterns and home range of tropical fishes are known.…”
Section: Discussionmentioning
confidence: 99%
“…Spotlighting was always conducted before electrofishing as it was considered to be relatively non‐invasive and unlikely to induce movement of fishes out of the surveyed area. Regular monthly spotlighting of giant kokopu in a small stream over many months did not result in significant movement out of surveyed pools (Hansen & Closs, 2005), whereas electrofishing has been observed to induce significant movement out of sampled reaches in salmonids (Peterson et al , 2004). All sampling was completed at times of low stable flow and at times when no rain fell within the stream catchments between spotlighting a reach and electrofishing of the same reach on the next day.…”
Section: Methodsmentioning
confidence: 99%